Aneurysm of the Common Iliac Artery Revealing a Behcet's Disease - M. Elqatni; J. Fatihi; N. Elomri; M. Jira; Y. Sekkach; T. Amezyane; K. Ennibi; A. Abouzahir (Journal of Hypertension and Cardiology, 2020)
A case report of a common iliac artery aneurysm revealing underlying Behçet’s disease. It reviews diagnostic clues, vascular complications, and multidisciplinary management.
Keywords: hypertension